Analisis Spasial Indeks Kedalaman Kemiskinan Tiga Provinsi di Pulau Jawa Tahun 2021 - Utama, Kharisma Pandu; Sari, Liza Kurnia (Politeknik Statistika STIS, 2023)
From 2014-2021, the poverty gap index in Indonesia shows a stagnant trend because poverty alleviation is still not focused on the poverty gap index (P1). Java Island, which is the center of government and economy, still has poverty problems. In 2019-2021 the poverty gap index (P1) for the Provinces of Central Java, Yogyakarta Special Region and East Java is always above the national figure and shows an upward trend. The purpose of this study is to see an overview and find out which variables significantly influence the district/city poverty gap index in the Provinces of Central Java, Yogyakarta Special Region, and East Java by considering spatial effects. The analytical method used is spatial regression with Spatial Error Model (SEM). Based on the results of the study, areas with a high poverty gap index were clustered in the northern region of East Java Province and the western region of Central Java Province. Variables that significantly affect the poverty gap index are GRDP per capita, the percentage of households using their own latrine, and the average length of schooling.